Survei IoT Healthcare Device - Yulia Suryandari (APIC, 2020)
The Internet of Things (IoT) has enormous potential in creating the value of life related to technology. IoT has various application domains, including in the health sector. IoT-based healthcare services are expected to reduce costs, improve quality of life, and enrich user experience. The presence of IoT devices for healthcare services can also avoid unnecessary hospitalization and ensure that patients who need health services get it quickly. This paper surveys advances in IoT-based health care technology and reviews the latest architectures / platforms, platforms, applications and industry trends in IoT-based healthcare solutions. Some IoT devices and prototypes in the healthcare field are also discussed in this paper. Through this paper, it is expected that readers can be known and discuss IoT devices in the healthcare sector.